Development and characterisation of novel durum wheat–H. chilense 4Hch chromosome lines as a source for resistance to Septoria tritici blotch - Cifuentes, Zuny; Calderón, Maria-Carmen; Miguel-Rojas, Cristina; Sillero, Josefina C.; Prieto, Pilar (Frontiers in Plant Science, 2024)
The use of wild species as a source of genetic variability is a valued tool in the framework of crop breeding. Hordeum chilense Roem. et Schult is a wild barley species that can be a useful genetic donor for sustainable wheat breeding which carries genes conferring resistance to some diseases or increasing grain quality, among others. Septoria tritici blotch (STB), caused by the Zymoseptoria tritici fungus, is one of the most important wheat diseases worldwide, affecting both bread and durum wheat and having a high economic impact. Resistance to STB has been previously described in H. chilense chromosome 4Hch. In this study, we have developed introgression lines for H. chilense chromosome 4Hch in durum wheat using interspecific crosses, advanced backcrosses, and consecutive selfing strategies. Alien H. chilense chromosome segments have been reduced in size by genetic crosses between H. chilense disomic substitution lines in durum wheat and durum wheat lines carrying the Ph1 deletion. Hordeum chilense genetic introgressions were identified in the wheat background through several plant generations by fluorescence in situ hybridisation (FISH) and simple sequence repeat (SSR) markers. An STB infection analysis has also been developed to assess STB resistance to a specific H. chilense chromosome region. The development of these H. chilense introgression lines with moderate to high resistance to STB represents an important advance in the framework of durum breeding and can be a valuable tool for plant breeders.